Acid-base relations in epithelium of turtle bladder: site of active step in acidification and role of metabolic CO(2) - Steinmetz, Philip T. (1969)
The acid-base relations across the two surfaces of the epithelium of the turtle bladder were examined. By means of the 5,5-dimethyl-2,4-oxazolidinedione (DMO) technique the intracellular OH(-) concentration was measured in the presence and absence of a transepithelial pH gradient. When both sides of the bladder were bathed with solutions free of exogenous CO(2) and bicarbonate at pH 7.41 ([OH(-)] = 239 nmoles/liter), the epithelial cells were alkaline, the mean intracellular [OH(-)] being 347nmoles/liter. This alkalinity of the cells was preserved in bladders that secreted H(+) against a gradient of over 2 pH units. In bathing solutions stirred with 4.85% CO(2) and buffered with 25 mM HCO(3)(-) at pH 7.41 the intracellular [OH(-)] was lower than in CO(2)-free solutions and close to the extracellular [OH(-)]. In the CO(2)-free system anaerobiosis caused increased alkalinity of the cells and inhibition of H(+) secretion presumably by decreased metabolic CO(2) production. Carbonic acid inhibitors reduced H(+) secretion, but had no significant effect on the alkalinity of the cells. An inactive analogue of acetazolamide had no effect on H(+) secretion. The results indicate that the active step in acidification is located near the mucosal surface of the epithelium and that the alkali formed within the epithelial cells moves passively into the serosal solution along an electro-chemical gradient. The inhibitory effect of certain sulfonamides on H(+) secretion by the bladder is directly correlated with their known carbonic anhydrase inhibitory activity, but not associated with a measurable change in the mean intracellular [OH(-)].